ON THE REPRESENTATION OF MODULES OVER FINITE CHAIN RINGS - Georgieva, Nevyana; Landjev, Ivan (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2017)
We define a standard form for matrices over finite chain rings and describe some basic operations on modules over such rings. These results are used as a tool for the investigation of network codes over finite chain rings and spreads in projective Hjelmslev geometries.